Comparison of CoQ10 & L-Carnitine In Remyelination of White Matter In A Rat Model of Multiple Sclerosis - Qureshi, Tayyaba; Ali, Shabana; Yasser, Ayesha; Hina, Mohtasham; Fahad, Tayyaba; Muqeet, Abdul (Journal of Rawalpindi Medical College, 2026)
Objective: To compare the therapeutic effects of Coenzyme Q10 & L-Carnitine on remyelination of Anterior Commissure in Cuprizone-induced rat model of Multiple Sclerosis. Methods: Forty male Sprague Dawley rats were randomly divided into four groups. Group 1 was given a normal diet, and the remaining three groups were Multiple Sclerosis models and given 0.2% Cuprizone for 12 weeks. After 4 weeks, Group 3 received 150 mg/kg/day CoQ10, Group 4 was given 100 mg/kg/day L-Carnitine, while Cuprizone poisoning continued till 12 weeks. Rats were then dissected, and their brains were removed. Coronal sections were stained with Luxol Fast Blue stain to demonstrate the remyelination. Results: CoQ10 was found to promote remyelination more effectively than L-Carnitine, as evidenced by significantly reduced areas of demyelination. Conclusion: CoQ10 demonstrates greater effectiveness in promoting remyelination compared to L-Carnitine. Keywords: Coenzyme Q10, Carnitine, Multiple Sclerosis, Remyelination